Mitochondrial function: A new direction for the targeted treatment of cardiovascular diseases with Chinese herbal medicine - Lin Yang; Liang Wang; Baofeng Yang; Yue Zhang (Journal of Holistic Integrative Pharmacy)
Mitochondria play a central role in cardiovascular diseases, primarily by providing cellular energy and facilitating various cardiac functions. Excessive fat accumulation, circadian rhythm disturbances, viral infections, and persistent inflammation can lead to myocarditis, fibrosis, and infarction, thereby exacerbating the progression of cardiovascular diseases. As essential organelles for energy production, mitochondria exhibit remarkable dynamic adaptability and can integrate diverse cellular signaling pathways, endowing myocardial cells with both bioenergetic and biosynthetic versatility. Consequently, targeting mitochondria for cardiovascular disease therapy has gained increasing attention and is applicable to various cardiovascular conditions. Numerous mitochondrial adaptive mechanisms, including dynamics, metabolic processes, and apoptosis regulation, have emerged as promising therapeutic targets. Nevertheless, contemporary investigations into mitochondrial biology have unveiled their intricate structural and functional characteristics, as well as their complex roles within cellular systems, which present obstacles to the clinical implementation of mitochondria-focused cardiovascular therapies. Recent studies have found that traditional Chinese medicine (TCM) possesses the potential to effectively address cardiovascular diseases while enhancing the structural integrity and functional capacity of mitochondria. This review aims to offer a comprehensive analysis of the modulatory effects of TCM on cardiac mitochondria and its therapeutic ramifications for cardiovascular conditions.